Complex Traveling-Wave and Solutions To The
Complex Traveling-Wave and Solutions To The
Complex Traveling-Wave and Solutions To The
Suppose that
𝜓(𝑥, 𝑡) = 𝑤(𝜉) = 𝑤(𝜅(𝑥 − 𝑐𝑡)) (11)
Next, inserting (11) into (8), and integrating it twice with respect to 𝜉, we get
2𝛽
𝑤(𝜉) = 𝜑 2 + 𝑎0 . (12)
(𝑐 2 −1)
−𝐶2
𝜙𝐴,11 (𝑥, 𝑡) = 𝐴1 (1 + 𝑖)√ 𝑠𝑒𝑐 (√−2𝐶2 𝜅(𝑥 − 𝑐𝑡)), (18)
𝐶4
2
2𝛽 −𝐶2
𝜓𝐴,11 (𝑥, 𝑡) = {𝐴 √ 𝑠𝑒𝑐 (√−2𝐶2 𝜅(𝑥 − 𝑐𝑡))} + 𝑎0 , (19)
(𝑐 2 − 1) 1 𝐶4
−𝐶2
𝜙𝐴,12 (𝑥, 𝑡) = 𝐴1 (1 + 𝑖)√ 𝑐𝑠𝑐 (√−2𝐶2 𝜅(𝑥 − 𝑐𝑡)), (20)
𝐶4
2
2𝛽 −𝐶2
𝜓𝐴,12 (𝑥, 𝑡) = {𝐴 √ 𝑐𝑠𝑐 (√−2𝐶2 𝜅(𝑥 − 𝑐𝑡))} + 𝑎0 , (21)
(𝑐 2 − 1) 1 𝐶4
𝐶2 2
Case 2: For 𝐶0 = , 𝑎𝑛𝑑 𝐶2 > 0, 𝐶4 > 0. From Set 2, complex trigonometric
4𝐶4
function solutions to (1) − (2) are obtained:
𝐶2
𝜙𝐴,13 (𝑥, 𝑡) = 𝐴1 (1 + 𝑖)√ 𝑡𝑎𝑛 (√𝐶2 𝜅(𝑥 − 𝑐𝑡)), (22)
2𝐶4
2
2𝛽 𝐶2
𝜓𝐴,13 (𝑥, 𝑡) = {𝐴 √ 𝑡𝑎𝑛 (√𝐶2 𝜅(𝑥 − 𝑐𝑡))} + 𝑎0 . (23)
(𝑐 2 − 1) 1 2𝐶4
1 𝛼𝛽𝐴1 2 2𝛼𝛽𝐴0 2 +𝑐 2 −1
𝐶4 = − , 𝑎0 − .
2 𝜅2 (𝑐−1)2 (𝑐+1)2 𝛼(𝑐−1)(𝑐+1)
𝜅(𝑥 − 𝑐𝑡)
𝐶2 𝑠𝑒𝑐ℎ2 (√2𝐶2 )
2
𝜙𝐴,14 (𝑥, 𝑡) = 𝐴0 (1 + 𝑖) + 𝐴1 (1 + 𝑖) , (24)
𝜅(𝑥 − 𝑐𝑡)
2√𝐶2 𝐶4 𝑡𝑎𝑛ℎ (√2𝐶2 ) − 𝐶3
2
2
𝜅(𝑥 − 𝑐𝑡)
𝐶2 𝑠𝑒𝑐ℎ (√2𝐶2
2
)
2𝛽 2
𝜓𝐴,14 (𝑥, 𝑡) = 𝐴 + 𝐴1 + 𝑎0 , (25)
(𝑐 2 − 1) 0 𝜅(𝑥 − 𝑐𝑡)
2√𝐶2 𝐶4 𝑡𝑎𝑛ℎ (√2𝐶2 ) − 𝐶3
2
{ }
2
2 𝜅(𝑥 − 𝑐𝑡)
2𝛽 𝐶2 𝐶3 𝑠𝑒𝑐ℎ (√2𝐶2 )
2
𝜓𝐴,16 (𝑥, 𝑡) = 𝐴 + 𝐴1 + 𝑎0 (29)
(𝑐 2 − 1) 0 𝜅(𝑥 − 𝑐𝑡)
2
𝐶2 𝐶4 (1 − 𝑡𝑎𝑛ℎ (√2𝐶2 2 )) − 𝐶3 2
{ }
1 2𝜅2 (𝑐 2 −1)−1
Set 1: 𝐴0 = 0, 𝐴1 = ±√− (𝑐 2 − 1)𝜅, 𝐵1 = 0, 𝑎0 = .
𝛼𝛽 𝛼
1 𝜅2 (𝑐 2 −1)+1
Set 2: 𝐴0 = 0, 𝐴1 = 0, 𝐵1 = ±√ (𝑐 2 − 1)𝜅, 𝑎0 = − .
𝛼𝛽 𝛼
To use (38) and considering the obtained results above, it is revealed the complex
solitons solutions to (1) − (2) as
1 2
𝜙𝐵,11 (𝑥, 𝑡) = ±(1 + 𝑖)√− (𝑐 − 1)𝜅𝑡𝑎𝑛(𝜅(𝑥 − 𝑐𝑡)), (34)
𝛼𝛽
2
2𝛽 1 2 2𝜅 2 (𝑐 2 − 1) − 1
(𝑥,
𝜓𝐵,11 𝑡) = 2 {√− (𝑐 − 1)𝜅𝑡𝑎𝑛ℎ(𝜅(𝑥 − 𝑐𝑡))} + . (35)
(𝑐 − 1) 𝛼𝛽 𝛼
1 2
𝜙𝐵,12 (𝑥, 𝑡) = ±(1 + 𝑖)√− (𝑐 − 1)𝜅𝑐𝑜𝑡ℎ(𝜅(𝑥 − 𝑐𝑡)), (36)
𝛼𝛽
2
2𝛽 1 2 2𝜅 2 (𝑐 2 − 1) − 1
𝜓𝐵,12 (𝑥, 𝑡) = 2 {√− (𝑐 − 1)𝜅𝑐𝑜𝑡ℎ(𝜅(𝑥 − 𝑐𝑡))} + . (37)
(𝑐 − 1) 𝛼𝛽 𝛼
1
𝜙𝐵,13 (𝑥, 𝑡) = ±(1 + 𝑖)√ (𝑐 2 − 1)𝜅𝑠𝑒𝑐ℎ(𝜅(𝑥 − 𝑐𝑡)) (38)
𝛼𝛽
2
2𝛽 1 2 𝜅 2 (𝑐 2 − 1) + 1
𝜓𝐵,13 (𝑥, 𝑡) {√ (𝑐 − 1)𝜅𝑠𝑒𝑐ℎ(𝜅(𝑥 − 𝑐𝑡))} − (39)
(𝑐 2 − 1) 𝛼𝛽 𝛼
1
𝜙𝐵 14 (𝑥, 𝑡) = ±(1 + 𝑖)√ (𝑐 2 − 1)𝜅 𝑖 𝑐𝑠𝑐ℎ(𝜅(𝑥 − 𝑐𝑡)) (40)
𝛼𝛽
2
2𝛽 1 2 𝜅 2 (𝑐 2 − 1) + 1
𝜓𝐵 14 (𝑥, 𝑡) {√ (𝑐 − 1)𝜅 𝑖 𝑐𝑠𝑐ℎ(𝜅(𝑥 − 𝑐𝑡))} − (41)
(𝑐 2 − 1) 𝛼𝛽 𝛼
(𝑐 2 − 1)(𝛼 𝑎0 + 1) 2(𝛼 𝑎0 + 1)
√ 𝑠𝑖𝑛 (√ (𝑥 − 𝑐𝑡))
2𝛼𝛽 (1 − 𝑐 2 )
𝜙𝑐,11 (𝑥, 𝑡) = ±(1 + 𝑖) (44)
2(𝛼 𝑎0 + 1)
(1 + 𝑐𝑜𝑠 (√ (𝑥 − 𝑐𝑡)))
(1 − 𝑐 2 )
(𝑐 2 − 1)(𝛼 𝑎0 + 1) 2(𝛼 𝑎0 + 1)
√ 𝑠𝑖𝑛 (√ (𝑥 − 𝑐𝑡))
2𝛽 2𝛼𝛽 (1 − 𝑐 2 )
𝜓𝐶,11 (𝑥. 𝑡) = + 𝑎0 , (45)
(𝑐 2− 1)
2(𝛼 𝑎0 + 1)
(1 + 𝑐𝑜𝑠 (√ (𝑥 − 𝑐𝑡)))
(1 − 𝑐 2 )
{ }
(𝑐 2 − 1)(𝛼 𝑎0 + 1) 2(𝛼 𝑎0 + 1)
√ 𝑠𝑖𝑛 (√ (𝑥 − 𝑐𝑡))
2𝛼𝛽 (1 − 𝑐 2 )
𝜙𝐶,12 (𝑥, 𝑡) = ±(1 + 𝑖) (46)
2(𝛼 𝑎0 + 1)
(−1 + 𝑐𝑜𝑠 (√ (𝑥 − 𝑐𝑡)))
2𝜅 2 (1 − 𝑐 2 )
(𝑐 2 − 1)(𝛼 𝑎0 + 1) 2(𝛼 𝑎0 + 1)
√ 𝑠𝑖𝑛 (√ (𝑥 − 𝑐𝑡))
2𝛽 2𝛼𝛽 (1 − 𝑐 2 )
𝜓𝐶,12 (𝑥, 𝑡) = + 𝑎0 , (47)
(𝑐 2− 1)
2(𝛼 𝑎0 + 1)
(−1 + 𝑐𝑜𝑠 (√ (𝑥 − 𝑐𝑡)))
2𝜅 2 (1 − 𝑐 2 )
{ }
2
2𝛽 (𝑐 2 − 1)(𝛼 𝑎0 + 1) (𝛼 𝑎0 + 1)
𝜓𝐶,13 (𝑥, 𝑡) = 2 {√ 𝑐𝑜𝑡 (√ (𝑥 − 𝑐𝑡)) } + 𝑎0 (49)
(𝑐 − 1) 2𝛼𝛽 2(1 − 𝑐 2 )
(𝑐 2 − 1)(𝛼 𝑎0 + 1) 2(𝛼𝑎0 + 1)
√ 𝑐𝑜𝑠 (√ (𝑥 − 𝑐𝑡))
2𝛼𝛽 (1 − 𝑐 2 )
𝜙𝐶,14 (𝑥, 𝑡) = ±(1 + 𝑖) (50)
2(𝛼𝑎0 + 1)
(1 ± 𝑠𝑖𝑛 (√ (𝑥 − 𝑐𝑡)))
(1 − 𝑐 2 )
2
(𝑐 2 − 1)(𝛼 𝑎0 + 1) 2(𝛼𝑎0 + 1)
√ 𝑐𝑜𝑠 (√ (𝑥 − 𝑐𝑡))
2𝛽 2𝛼𝛽 (1 − 𝑐 2 )
𝜓𝐶,14 (𝑥, 𝑡) = + 𝑎0, (51)
(𝑐 2 − 1) 2(𝛼𝑎0 + 1)
(1 ± 𝑠𝑖𝑛 (√ (𝑥 − 𝑐𝑡)))
{ (1 − 𝑐 2 ) }
(𝑐 2 − 1)(𝛼 𝑎0 + 1) 2(𝛼 𝑎0 + 1)
√ 𝑐𝑜𝑠 (√ (𝑥 − 𝑐𝑡))
2𝛼𝛽 (1 − 𝑐 2 )
𝜙𝐶,15 (𝑥, 𝑡) = ±(1 + 𝑖) (52)
2(𝛼 𝑎0 + 1)
(−1 ± 𝑠𝑖𝑛 (√ (𝑥 − 𝑐𝑡)))
2𝜅 2 (1 − 𝑐 2 )
2
(𝑐 2 − 1)(𝛼 𝑎0 + 1) 2(𝛼 𝑎0 + 1)
√ 𝑐𝑜𝑠 (√ (𝑥 − 𝑐𝑡))
2𝛼𝛽 (1 − 𝑐 2 )
2𝛽
𝜓𝐶,15 (𝑥, 𝑡) = + 𝑎0 , (53)
(𝑐 2− 1)
2(𝛼 𝑎0 + 1)
−1 ± 𝑠𝑖𝑛 (√ (𝑥 − 𝑐𝑡))
(1 − 𝑐 2 )
{ ( ) }